Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/jimse-09-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Joint estimation of SOC and SOH for lithium-ion batteries based on EKF multiple time scales

Abstract: PurposeThe operation state of lithium-ion battery for vehicle is unknown and the remaining life is uncertain. In order to improve the performance of battery state prediction, in this paper, a joint estimation method of state of charge (SOC) and state of health (SOH) for lithium-ion batteries based on multi-scale theory is designed.Design/methodology/approachIn this paper, a joint estimation method of SOC and SOH for lithium-ion batteries based on multi-scale theory is designed. The venin equivalent circuit mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It has been found that the optimal temperature should be kept within a narrow variation of 20–45°C. Therefore, battery thermal management system (BTMS) must be well designed to control the battery temperature within the safe range (Li et al , 2020; Shi et al , 2021; Teng et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the optimal temperature should be kept within a narrow variation of 20–45°C. Therefore, battery thermal management system (BTMS) must be well designed to control the battery temperature within the safe range (Li et al , 2020; Shi et al , 2021; Teng et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, various methods, such as the total leastsquares algorithm for capacity estimation, 8 hybrid neural networks, 9 and improved long short-term memory (LSTM) algorithms, 10 have been studied to estimate the SOH. 11,12 Accordingly, original equipment manufacturers manufacture eco-friendly vehicles that demand certain accuracies in terms of the SOC and SOH, that is, typically within 5% and 10% for the SOC and SOH, respectively. Several studies and patents related to SOC and SOH estimation algorithms exist; however, accuracy standards have not been stipulated.…”
Section: Introductionmentioning
confidence: 99%
“…These include OCV, model‐based, data‐driven, hybrid, 6 and combined methods 7 . In addition, various methods, such as the total least‐squares algorithm for capacity estimation, 8 hybrid neural networks, 9 and improved long short‐term memory (LSTM) algorithms, 10 have been studied to estimate the SOH 11,12 . Accordingly, original equipment manufacturers manufacture eco‐friendly vehicles that demand certain accuracies in terms of the SOC and SOH, that is, typically within 5% and 10% for the SOC and SOH, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Extended Kalman filter (EKF) and unscented Kalman filter (UKF) are introduced to expand their applications into nonlinear systems. [15][16][17] These methods effectively eliminated the process noise and measurement noise, and robust SOC information is provided based on the battery state-space analysis. However, the implementation of the algorithm is complex and complicated for the use of the mass of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional KF method is only suitable for linear systems. Extended Kalman filter (EKF) and unscented Kalman filter (UKF) are introduced to expand their applications into nonlinear systems 15‐17 . These methods effectively eliminated the process noise and measurement noise, and robust SOC information is provided based on the battery state‐space analysis.…”
Section: Introductionmentioning
confidence: 99%